Strengthening Islamic character through Mathematics learning - Muhammad Istiqlal; Jumadi Jumadi (Prodi PGMI IAIN Salatiga, 2017)
The concept of mathematics learning which is integrated with Islamic character education is still limited; this is one of logical reasons why this research is conducted. The basic motivation of carrying out this research is to describe a concept of mathematics learning which is contextualized with Islamic character education. This research aims at describing concept of mathematics learning which is integrated with Islamic character education. This research uses a qualitative approach by emphasizing its analysis on the comparative inference process as well as on phenomena relationship dynamics observed by using scientific logic. Qualitative research is an approach that produces descriptive data in the form of written words from observed people that are not written in terms used in quantitative research. Research method used in this study is case study in which the researcher is trying to find out how the process of strengthening Islamic character through mathematics learning. This research was carried out at MA Nurul Ummah Kotagede Yogyakarta which has innovatively implemented mathematics learning using various methods through interactive learning multimedia which is integrated with strengthening Islamic character. Research finding showed that strengthening Islamic character through mathematics learning at MA Nurul Ummah is integrated into several aspects, namely learning methods, learning materials, and all aspect directly related to learning process in the classroom including putting statement of honesty on the answer sheet and giving reward and punishment to students.